Upaya Peningkatan Produksi Ternak Kambing melalui Manajemen Kesehatan, Reproduksi, dan Pelayanan - Purba, Fika Yuliza; Yusuf, Muhammad; Nurdin, Muhammad Ardiansyah; Masturi, Masturi; Bahmid, Nur Alif; Nur, Muhammad Muflih; Yusuf, Subaedy; Ismail, Irwan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this community service was to improve the quality of goat in Kalimporo Village, Bangkala District, Jeneponto Regency, through dissemination of health management, reproductive management and animal health service. Methodology: The community service was carried out by counselling method, evaluated by a pre- and post-test questionnaire, the development of the goat health and reproductive handbook and posters, and the animal health examination in the field. Results: The activity was carried out on June 1-2, 2024, involving 35 goat farmers in the counselling session, and 465 goats in the animal health service session. In the end of the counselling session, the results showed that the farmers’ knowledge regarding animal health and reproductive management were 46.85% and 54.85%, respectively. The goat health and reproductive handbook and posters was developed and distributed to farmers. The examination of the animal health discovered that the digestive disorders were the most common diseases in goats. Animal health service was carried out by providing anthelminthic drugs and vitamins. Conclusions: The community service activity slightly increased the level of farmer’s knowledge on the animal health and reproductive management. Limitations: The limitations of this community service activity are the limited number of participating farmers and interaction time with the community. Contribution: This community service activity can be useful for building human resources in the goat farming sector, especially in Kalimporo Village to develop goat farming system through efficient health and reproductive management.